Intra-Articular Mesenchymal Stem Cells Versus Hyaluronic Acid In Knee Osteoarthritis: A Systematic Review Of Randomized And Controlled Trials - I Gede Pradnya Wisnu Murthi; Putu Kermawan (Green Publisher Indonesia, 2026)
Knee osteoarthritis (KOA) is a progressive degenerative joint disease associated with pain, functional limitation, and reduced quality of life. Conventional treatments such as intra-articular hyaluronic acid (HA) provide symptomatic relief but lack regenerative capacity. Mesenchymal stem cells (MSCs) have emerged as a potential disease-modifying therapy due to their regenerative and immunomodulatory properties. The objective was to systematically review and compare the efficacy and safety of intra-articular MSC therapy versus HA in the management of KOA.This systematic review was conducted following PRISMA guidelines. Literature searches across multiple databases identified randomized clinical trials (RCTs) comparing MSC therapy with HA in KOA patients. Outcomes assessed included pain (VAS) and functional scores (WOMAC). Follow-up durations ranged from 6 months to 4 years. A systematic review was conducted using seven clinical studies, including RCT and phase I/II trials. Across all included studies, MSC therapy demonstrated superior clinical outcomes compared to HA. Significant improvements were consistently observed in pain reduction and functional scores. All RCT showed greater reductions in WOMAC and VAS scores with MSCs compared to HA.The superior clinical outcomes observed with MSC therapy compared to HA may be attributed to its regenerative and immunomodulatory properties, which extend beyond the viscosupplementation effect of HA. MSCs not only reduce inflammation but also promote cartilage repair, contributing to sustained improvements in pain and function. Variability in cell sources, dosing regimens, and study designs across RCT may influence the observed outcomes.